Peningkatan Purchase Intention Dalam Peran e-WOM dan Celebrity Endorser Pada Produk Skincare Internasional - Caroline Marninda; Erilia Kesumahati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research was conducted to determine the impact of e-WOM and celebrity endorsers in influencing purchase intention, which is consumer behavior in showing interest in purchasing international skincare brands mediated by brand awareness which focuses on the people of Batam City. The variables tested in this study include e-WOM, celebrity endorser, purchase intention, and brand awareness. This study tested 244 out of 267 respondent data with the help of the SmartPLS application. After the data was analyzed with the application, several tests were carried out to obtain the required research results. The results of the analysis state that e-WOM and celebrity endorsers can influence brand awareness positively as evidenced by the t-statistic value which reaches more than 1.96 and the p-value which is less than 0.05. E-WOM, celebrity endorsers, and brand awareness have also been proven to be able to influence purchase intention positively. The mediating role of brand awareness is proven to have a positive influence between the relationship between e-WOM and purchase intention. However, mediation by brand awareness does not have a significant influence on the relationship between celebrity endorsers and purchase intention, as evidenced by the t-statistic value which does not reach 1.96 and the p-value which is more than 0.05.